Entreprise de légitimation et de délégitimation des savoirs scolaires et « de terrain » dans l’univers du travail social - Jean-François Gaspar (Cahiers de la Recherche sur l'Education et les Savoirs)
This text draws from the observation of social workers’ practices, of what they say about them and of their relationship to forms of knowledge drawn from school and their field practice. Two groups among others are examined: clinical and militant social workers. The first group, almost exclusively made up of women, has had a short brush with university studies. These workers negate the technical knowledge conveyed by the social work schools, value reflection, and more still introspection, beyond what is asked for by users and psychology. They refer to the psychologists with whom they work and give primacy to supervision and short training sessions. The second group comes from the militant world (parties, unions, associations), and have often been through shorter and more chaotic schooling. They distrust schools and established knowledge, but value self-learning, which is a characteristic of the universe of militancy.